New Delhi Response to Beijing ‘BRI’ Project: A Lucid connection with Chinese “String of Pearls” - Hafeez Ullah Khan; Dr. Ijaz Khalid (Journal of Political Studies, 2018)
Indian percepts of China are biased by dread of Chinese hegemony; at present, many individuals in Indian security establishment has positioned China a greater menace than ever before. This paper investigates Sino-India relationship and Indian responses to Chinese ‘OBOR’ (One Belt, One Road) project by examining the extent and nature of their relationship within the diplomatic, geopolitical, economic, and defense spheres. There is power struggle between China and India for the dominance on Indian Ocean. The Indians perceive Chinese Maritime Silk Road projects as Indian encirclement with the development of ports projects in Indian Ocean, which are part of Chinese “String of Pearls” strategy. Chinese military naval ships and submarine presence in the number of ports around the Indian Ocean has made India anxious, the Indian policy experts perceive it as a threat to their national security and interest. From the Chinese perspective, ‘String of Pearls’ is a doctrine to free China from its Malacca dilemma. In Foreign Policy, the beginning of wisdom is to understand what the other party conceives, and why. And this is just as important for our Chinese friends as for the Indians